Design Improvements of Vane Bearing Compressor. Issue 1 (September 2021) - Hu, YS; Wei, H J; Xu, J; Wan, P K; Ren, L P; Fu, Z
Abstract: A variant of vane bearing compressor with double rolling bearing had been introduced two years ago (Hu and Xu, 2019). In order to solve the problems of complex assembly process and abnormal wear in the vane bearing compressor with double rolling bearing, this paper presents a type of improved vane bearing compressor with single rolling bearing. The improved vane bearing compressor integrates the rolling bearings and the cylinder into a rolling bearing cylinder unit. The suction t and discharge ports are placed on the end face of the main bearing. With these improvements, the number of the end face friction pairs of rolling bearing inner ring is reduced by half, the number of parts is reduced accordingly, and the assembly process is thus made simpler than that with double rolling bearing. This paper introduces the operational characteristics and makes a series of structure optimization to improve the performance of the improved vane bearing compressor with single rolling bearing. The energy efficiency of the improved vane bearing compressor with single rolling bearing is found to be 5% higher than that with the double rolling bearing.